Edu-eco Park at Bukit Serindit, Melaka - Hussain, Norhuzailin; Hussein, Mohd Kher; Leng, Li Thing (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
Park gives many benefits for people such as for socialization and integration, well-being, environmental and economic. The purpose of this study is to highlight the importance of green environment and wildlife conservation where people need to experience and value it, and recommend some designs to overcome the issues which can be used for Landscape architects in Malaysia related to the similar site’s condition. The methods used here is by reviewing and analysing the final year student project based on her site observations including the inventory and analysis studies. Currently, The Bukit Serindit Recreational Park Melaka facing issues related to design such as underutilise, lack of connectivity between nodes, limit users to access the park; potential space are not well developed, effects the lacking of characteristics and space for outdoor activity; and reclamation of paddy field for residential purposes lead to reducing of green space. Edu-eco Park is chosen as a concept in the design by introducing more activities and facilities related to education and ecology approach to the park. This concept is to enriching the park in terms of human activities and the existing biodiversity in order to give solution to the lack of connectivity, under utilisation and reduction of green space issues. Thus, it is expected this park can sustain for future generation, and to become a new landmark and tourist spot in 2025; as well as the first Edu-eco Park in Melaka.